A4.5 Arthritis induces early bone high turnover, structural degradation and mechanical weakness. (13th February 2015) - Vidal, B; Cascão, R; Vale, AC; Cavaleiro, I; Vaz, MF; Brito, JA; Canhão, H; Fonseca, JE
Abstract : Background and objectives: We have previously found in the chronic SKG mouse model of arthritis that long standing (5 and 8 months) inflammation directly leads to high collagen bone turnover, disorganisation of the collagen network, disturbed bone microstructure and degradation of bone biomechanical properties. The main goal of the present work was to study the effects of the first days of the inflammatory process on the microarchitecture and mechanical properties of bone. Methods: Twenty eight Wistar adjuvant-induced arthritis (AIA) rats were monitored during 22 days after disease induction for the inflammatory score, ankle perimeter and body weight. Healthy non-arthritic rats were used as controls for comparison. After 22 days of disease progression rats were sacrificed and bone samples were collected for histomorphometrical, energy dispersive X-ray spectroscopical analysis and 3-point bending. Blood samples were also collected for bone turnover markers. Results: AIA rats had an increased bone turnover (as inferred from increased P1NP and CTX1, p = 0.0010 and p = 0.0002, respectively) and this was paralleled by a decreased mineral content (calcium p = 0.0046 and phosphorus p = 0.0046). Histomorphometry showed a lower trabecular thickness (p = 0.0002) and bone volume (p = 0.0003) and higher trabecular separation (p = 0.0009) in the arthritic group as compared with controls. In addition, bone mechanical tests showed evidence of fragility as depicted by diminished values of yield stress and ultimate fracture point (p = 0.0061 and p = 0.0279, respectively) in the arthritic group. Conclusions: We have shown in an AIA rat model that arthritis induces early bone high turnover, structural degradation, mineral loss and mechanical weakness.